Depot testosterone in boys with anorchia or gonadotrophin deficiency: effect on growth rate and adult height. Issue 2 (February 1991) - Moorthy, B; Papadopolou, M; Shaw, D G; Grant, D B
Abstract : Eleven teenage boys with bilateral anorchia and 12 with gonadotrophin deficiency were treated by injections of testosterone ester (enanthate) at an initial dose of 100 mg every six to eight weeks, rising to 250 mg every four weeks after three to four years. In the anorchic boys average adult height was 177.1 cm, compared with a mean mid-parental height of 174.4 cm, and mean predicted adult heights of 177.0 cm (Tanner-Whitehouse method) and 178.0 cm (Bayley-Pinneau method). In the patients with gonadotrophin deficiency, mean adult height was 176.9 cm, compared with a mean mid-parental height of 176.1 cm, and mean predicted adults heights of 174.0 cm (Tanner-Whitehouse method) and 177.3 cm (Bayley-Pinneau method). We conclude that this testosterone regimen allows achievement of full growth potential in such patients.